ANALISIS USER EXPERIENCE PADA GAME MOBILE LEGEND VERSI 1.4.14.4454 DENGAN MENGGUNAKAN GAME-DESIGN FACTOR QUESTIONNAIRE - Miftahul Huda (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2020)
This research tries to analyze user experience on legend mobile games. This study also supports providing an evaluation of the analysis of the game to improve the level of acceptance of online game users. The object of this research is the legend of online mobile games. This research was conducted in the application of quantitative methods in the application of quantitative descriptive. Legend mobile online games were analyzed using questionnaire game design factors with research variables namely Game Goals, Game Mechanisms, Interactions, Freedom, Fantasy Games, Narratives, Sensations, Game Values, Challenges, Social, Mysteries and Flow. Sampling in this study uses non-probability sampling technique that is sampling technique that does not provide equal opportunities for everyone or members who use a sample with 100 respondents. The results of this study indicate in general the legend of online mobile game applications is very evident from the results of the analysis of respondent responses. Of 76%, freedom with a percentage, 77%, and fantasy games with a percentage, 75%.